Prinsip An-Taradhin dalam Transaksi Jual Beli Perspektif Hadis Tematik dan Hukum Islam - Andi Tenritappu; Muhammadiyah Amin; Abdul Rahman Sakka; Muh Tabran (STAI DDI Kota Makassar, 2026)
This study aims to examine the normative and practical background of the principle of mutual consent (an-taradhin) in muamalah transactions from the perspective of Islamic law. The method used is qualitative research based on library research with a textual and contextual approach to the hadiths narrated by Ibn Majah and other similar chains of transmission. The results of the study indicate that in Islamic jurisprudence, the principle of an-taradhin is not merely a formal aspect but an absolute legal instrument to prevent practices of injustice, fraud (tadlis), uncertainty of information (gharar), and coercion (ikrah). In a modern context, the implementation of this principle requires transparency regarding product information, freedom of choice (khiyar), and legal awareness on both sides to ensure transactional justice. Theologically and sociologically, fulfilling this pillar of consent serves to maintain the economic stability of the community and ensure blessings in every activity related to meeting life’s necessities. The research conclusion affirms that an-taradhin is the primary filter and an absolute requirement for the validity of a contract. If this element of consent is lost due to coercion, manipulation, or hoarding of goods (ihtikar), then the transaction is automatically considered legally defective, invalid, or null and void according to Sharia.